Effect of parenchymal uptake of perfluorobutane microbubbles (Sonazoid®) on radiofrequency ablation of the liver: in vivo experimental study. (15th March 2016) - Min, Ji Hye; Kim, Young‐sun; Rhim, Hyunchul; Lee, Min Woo; Kang, Tae Wook; Song, Kyoung Doo; Lim, Hyo Keun
Abstract: Background & Aims: To investigate the differences in mechanical effects and ablation zone between radiofrequency (RF) ablation with and without Sonazoid uptake in an in vivo rabbit liver model. Methods: Our study was approved by the Institutional Animal Care and Use Committee. Twenty‐five rabbits were randomly allotted to one of five ablation durations (i.e., 1, 2, 3, 6 and 12 min). For each rabbit, RF ablation was performed twice, before and 10 min after Sonazoid administration (i.e. control group vs. Sonazoid group), using a 1‐cm internally cooled electrode (40W) equipped with a parallelly fixed pressure‐monitoring device. During ablation, a 'popping' sound was perceived and recorded along with tissue pressure changes and RF ablation parameters. Then, the ablation volume and microscopic changes were compared. Results: Popping sounds were more frequently perceived in the control group (21/25 vs. 1/25, P < 0.001). The time to first pressure peak was shorter in the Sonazoid group (22.3 ± 1.1 s vs. 46.3 ± 4.4 s, P < 0.001) with similar pressures (39.8 ± 4.2 mmHg vs. 35.6 ± 4.1 mmHg, P = 0.350). Time to first roll‐off and mean power output were significantly less in the Sonazoid group (17.6 ± 1.2 s vs. 71.2 ± 8.2 s, P < 0.001; 9.4 ± 0.3 W vs. 12.8 ± 0.5 W, P < 0.001). Consequently, the Sonazoid group had lower total energy and ablation volumes for all durations. Microscopically, the control group showed larger conflu‐ent disruptions, whereas the Sonazoid group showed many smaller disruptions scattered throughout the ablation zones. Conclusions: Radiofrequency ablation after Sonazoid uptake induces a smaller ablation zone than conventional RF ablation. However, it appears to ablate the liver tissue with less mechanical effects.